2018
DOI: 10.1093/annonc/mdy137
|View full text |Cite
|
Sign up to set email alerts
|

Selective RET kinase inhibition for patients with RET-altered cancers

Abstract: BackgroundAlterations involving the RET kinase are implicated in the pathogenesis of lung, thyroid and other cancers. However, the clinical activity of multikinase inhibitors (MKIs) with anti-RET activity in RET-altered patients appears limited, calling into question the therapeutic potential of targeting RET. LOXO-292 is a selective RET inhibitor designed to inhibit diverse RET fusions, activating mutations and acquired resistance mutations.Patients and methodsPotent anti-RET activity, high selectivity, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
313
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 337 publications
(316 citation statements)
references
References 25 publications
2
313
0
1
Order By: Relevance
“…Similar approaches could be feasible in DTCs with rearrangements involving ALK, 0.6-2.2% of all PTC and 1% in our series (29,30). Furthermore, LOXO-292 and BLU-667, selective and potent RET inhibitors (31,32), are currently being studied in Phase1/2 trials. LOXO-292 demonstrates robust anti-tumor activity in RET fusion positive thyroid cancer, according to interim clinical data reported at the 2018 American Thyroid Association annual meeting.…”
Section: Discussionmentioning
confidence: 75%
“…Similar approaches could be feasible in DTCs with rearrangements involving ALK, 0.6-2.2% of all PTC and 1% in our series (29,30). Furthermore, LOXO-292 and BLU-667, selective and potent RET inhibitors (31,32), are currently being studied in Phase1/2 trials. LOXO-292 demonstrates robust anti-tumor activity in RET fusion positive thyroid cancer, according to interim clinical data reported at the 2018 American Thyroid Association annual meeting.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, newer RET inhibitors, specifically those that are more selective for RET, such as LOXO-292 (22) and BLU-667 (12), are currently in clinical testing. Preliminary data have shown that these drugs have increased activity and improved tolerability compared with multikinase inhibitors, including RXDX-105 (23).…”
Section: Discussionmentioning
confidence: 99%
“…34 It is notable that the studies Furthermore, its use in a patient with advanced sMTC with a confirmed somatic RET M918T mutation resulted in tumour regression, a drop in serum calcitonin and symptom improvement. 35 The second drug, BLU-667, is also a selective RET inhibitor still in phase 2 trials; however, once again preliminary data have shown a good response in a patient with sMTC and multiple RET mutations. 36 Clearly, it is too early to draw conclusions on the efficacy of these novel drugs or the relative effects in patients with different RET mutations; however, these preliminary results are promising.…”
Section: Somatic Ret Mutationsmentioning
confidence: 99%